2022
DOI: 10.48550/arxiv.2205.07809
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Searching for a Ringdown Overtone in GW150914

Eliot Finch,
Christopher J. Moore

Abstract: We reanalyze the GW150914 post-merger data searching for quasinormal modes beyond the fundamental, quadrupolar mode. There is currently an ongoing disagreement in the literature about whether, and to what extent, the data contains evidence for a quasinormal mode overtone. We use a frequency-domain approach to ringdown data analysis that was recently proposed by the authors. Our analysis has several advantages compared to other analyses performed mainly in the time domain; in particular, the source sky position… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…This led to a test of the no-hair theorem at the ∼ 20% level. Recently, Cotesta et al [53] raised an opposing viewpoint that the search for the first overtone in the ringdown of GW150914 might be impacted by noises, therefore the conclusion still remains controversial [54,55]. On the other hand, Capano et al [56] studied the QNM spectrum of GW190521 [57] and found the l = m = 3 harmonic.…”
mentioning
confidence: 99%
“…This led to a test of the no-hair theorem at the ∼ 20% level. Recently, Cotesta et al [53] raised an opposing viewpoint that the search for the first overtone in the ringdown of GW150914 might be impacted by noises, therefore the conclusion still remains controversial [54,55]. On the other hand, Capano et al [56] studied the QNM spectrum of GW190521 [57] and found the l = m = 3 harmonic.…”
mentioning
confidence: 99%
“…For instance, [19] concludes that for precessing binary systems, linear QNMs do not always fit well GW signals from NR simulations starting from the merger time. Nevertheless, these results have motivated the use of the entire post-merger signal of current GW events, such as GW150914 [20], to detect the fundamental QNM (n = 0) as well as the first overtone (n = 1), and to perform tests of gravity [8,[21][22][23], although different conclusions have been obtained [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the linear QNM spectrum has been used to analyze current GW detections [17][18][19], forecast the future detectability of ringdown [20][21][22], and perform tests of gravity in the strong field regime [23,24].…”
mentioning
confidence: 99%